(3GdETGQGJ aj GdRjGQGJs - (3Ydj Hf CHj HcQ Hf Ydj GdgQhj, CHh GdMSf,J (B611 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfg SCdfi HYV GdENhGf GdUGdMjf s
(3BNQgG (B:s
(3hhSeJg HcJGH efGRd GdCQV PGJ GdWhd hGdYQV ef GQGO Pdc adjWdHg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B47s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B96s
Keywords: (3GdLZQGajG h GdHdOGfs